Pengaruh Disiplin Kerja, Lingkungan Kerja, dan Kompensasi Terhadap Kinerja Karyawan: Studi Kasus Pada Tenaga Kependidikan UNISBA Blitar - Ghina Nabilah; Sabri Armi Haqi (International Forum of Researchers and Lecturers, 2024)
This research aims to (1) determine the influence of work discipline on the performance of education staff at Unisba Blitar. (2) to determine the influence of the work environment on the performance of educational staff at Unisba Blitar. (3) to determine the effect of compensation on the performance of educational staff at Unisba Blitar. (4) to determine the influence of work discipline, work environment, and compensation simultaneously on the performance of educational staff at Unisba Blitar. The type of research used is explanatory research. The population in this study was the Education Personnel at the Balitar Islamic University (UNISBA) Blitar with a total of 88 Education Personnel. The data collection technique uses a questionnaire which is tested with validity and reliability tests. The data analysis technique used is multiple linear regression analysis. Based on the t test, it is known that the t count of the work discipline variable is 3,681, the work environment variable is 2,155, the compensation variable is 3,349, and the F-count value is 229,750. Based on the results of research conducted, it shows that (1) Work discipline has a positive and significant effect on employee performance. (2) The work environment has a positive and significant effect on employee performance. (3) Compensation has a positive and significant effect on employee performance. (4) Work discipline, work environment, and compensation simultaneously influence employee performance.